Panorama tecnológico colombiano: Una aproximación desde las solicitudes de patentes en Colombia entre los años 2000 y 2018 - Romero-Betancur, Jesus David (Revista Científica, 2021)
One aspect that allows us to recognize the extent to which innovation is promoted in a country corresponds to the number of patents requested and granted by it, understanding that in this way the dynamics in which knowledge is generated and appropriated for industrial and industrial purposes can be recognized. In this context, it seeks to establish a Colombian technological panorama, based on the patents presented between the years 2000 to 2018, according to the associated holders as well as their origin and nature as a natural or legal person (companies or universities). As a result of this exercise, the general perception that developments associated with the pharmaceutical sector are mainly protected in the country, finding that this occurs in the case of non-resident holders in the country, while in the case of residents the greater interest is generated by natural persons without a specific technical specialty; On the other hand, it is found that patents do not necessarily represent a factor of competitiveness in the market, but rather a factor of status or distinction in the case of nationals and a tool of market protection for foreigners, the latter especially given that the vast majority of objects of patent protection are not manufactured in the country, they are only marketed.